Multiplexed methylation profiles of tumor suppressor genes and clinical outcome in oligodendroglial tumors. (1st July 2016) - Kuo, Lu‐Ting; Lu, Hsueh‐Yi; Lee, Chien‐Chang; Tsai, Jui‐Chang; Lai, Hong‐Shiee; Tseng, Ham‐Min; Kuo, Meng‐Fai; Tu, Yong‐Kwang
Abstract: Aberrant methylation has been associated with transcriptional inactivation of tumor‐related genes in a wide spectrum of human neoplasms. The influence of DNA methylation in oligodendroglial tumors is not fully understood. Genomic DNA was isolated from 61 oligodendroglial tumors for analysis of methylation using methylation‐specific multiplex ligation‐dependent probe amplification assay (MS‐MLPA). We correlated methylation status with clinicopathological findings and outcome. The genes found to be most frequently methylated in oligodendroglial tumors were RASSF1A (80.3%), CASP8 (70.5%), and CDKN2A (52.5%). Kaplan–Meier survival curve analysis demonstrated longer duration of progression‐free survival in patients with 19q loss, aged less than 38 years, and with a proliferative index of less than 5%. Methylation of the ESR1 promoter is significantly associated with shorter duration of overall survival and progression‐free survival, and that methylation of IGSF4 and RASSF1A is significantly associated with shorter duration of progression‐free survival. However, none of the methylation status of ESR1, IGSF4, and RASSF1A was of prognostic value for survival in a multivariate Cox model. A number of novel and interesting epigenetic alterations were identified in this study. The findings highlight the importance of methylation profiles in oligodendroglial tumors and their possible involvement in tumorigenesis. Abstract : A multiplexed approach was used to investigate the methylation status of 24 genes in 61 human oligodendroglial tumors and their association with clinical outcome was analyzed. These findings highlight the importance of these potential biomarkers and their promoter regions on chromosomes and their possible involvement in tumorigenesis.